Infants of diabetic mothers: an Iraqi Teaching Hospital experience - Hameed, Numan N. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Despite significantly increased input from multidisciplinary teams during antenatal period, pregnancy outcome from women with type 1, type 2 and gestational diabetes mellitus (DM) remain substantially worse than that of general obstetric population. In Iraq, the true magnitude of infant of diabetic mother (IDM) is not well known as health system has been badly eroded over the period of gulf wars and sanctions.Objectives: to through a light on IDM in the maternity ward and neonatal care unit (NCU) of Baghdad Teaching Hospital, Medical city complex, Baghdad. Patients & Methods: A total of 120 IDM admitted to the maternity ward and (NCU) of Baghdad Teaching Hospital, Medical city complex, Baghdad, Iraq, were included in this descriptive study during the period 1st Jan. 2006 to 1st Jan. 2009. A questionnaire was filled for each neonate, which included maternal and neonatal information. Results were presented in frequencies. Multiple logistic regression was done to identify factors associated with death of IDM.Results: Gestational diabetes was the common type (60.8%), cesarean section was a common mode of delivery (81.7%) and (84.2%) of mothers got antenatal care visits. Regarding the neonates, prematurity was observed in (26.7%), macrosomia in (26.7%), hypoglycemia in (56.8%), hyperbilirubinaemia in (26.1%),congenital anomalies in (12.5%) and Sepsis in (11.4%) of the neonates. Mode of delivery and prematurity significantly affect the death of neonates (p = 0.036 and 0.0008), while parity, type of DM, and birth weight were not significantly affecting the outcome of IDM.Conclusions: High rates of hypoglycemia , Hyperbilirubinemia, prematurity, congenital anomalies and macrosomia were reported. The mode of delivery and prematurity significantly affect the death of IDM. Better perinatal care of mothers and their IDM with tighter preconceptual glycemic control is likely to reduce the prevalence of reported complications and death and improve the outcome for IDM.